2018
DOI: 10.1002/jccs.201700329
|View full text |Cite
|
Sign up to set email alerts
|

Combining of intelligent models through committee machine for estimation of wax deposition

Abstract: Deposition of the wax is one of the thorny issues in the petroleum industry, invoking costly problems during the transportation and production of crude oil. Owing to its devastating impacts on oil companies' economy, it is essential to develop a simple and robust strategy for the quantitative estimation of wax deposition. In this paper, support vector regression (SVR) is first proposed to estimate the amount of wax deposition. Subsequently, an artificial neural network (ANN) is developed for wax deposition pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Therefore, when different predictive models are available for the estimation of the response variable, this method produces combined models reaping the benefits of individual models. Studies have indicated that the committee machine is more accurate than individual models (Gholami et al , 2018(Gholami et al , 2020.…”
Section: Committee Machinementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when different predictive models are available for the estimation of the response variable, this method produces combined models reaping the benefits of individual models. Studies have indicated that the committee machine is more accurate than individual models (Gholami et al , 2018(Gholami et al , 2020.…”
Section: Committee Machinementioning
confidence: 99%
“…For longitudinal dispersion coefficient modeling considering interrelated influencing parameters, a proper selection of input parameters is important (Dehghani et al 2020). Since an intelligent model learns the relationship between input variables and the output variable, it can estimate the target value in unseen data (Gholami et al 2014b(Gholami et al , 2018 The performance in computing the longitudinal dispersion coefficient was judged by using two criteria as given by Equations ( 3)-( 6): where Y i obs is the measured value of sample i, Y i pred is the estimated value of sample i, Ŷobs is the average of real values, and n is the number of samples. When the values of MSE, MAE, and PB are close to zero and the value of R 2 is close to 1, a model with superior performance is achieved.…”
Section: Data Input/output Spacementioning
confidence: 99%
“…The Binbinzong formula (Ding Fig. 4 Changqing crude oil viscosity-temperature curve selected the pipeline flow, upstream outbound oil temperature, downstream-inlet oil temperature, and ground temperature along the line as the modeling parameters, and used the gray correlation method (Gholami et al 2018) and correlation formula analysis to determine the influence of the pipeline's friction factors. The predicted results are shown in Table 5 and indicate that the flow rate of the SCADA system data, the upstream-outlet oil temperature, and the downstream-inlet oil temperature are the main influencing factors of the pipeline friction, whereas the ground temperature correlation is small.…”
Section: Influencing Factor Selectionmentioning
confidence: 99%
“…In recent years, scholars have created pipeline wax prediction models based on data mining. Gholami et al (2018) and Xie and Xing (2017) used support vector regression (SVR) to estimate wax deposition, developed a human ANN, and constructed a mixed model of SVR and ANN. The analysis and acquisition of a hybrid model optimized using the genetic algorithm (GA) can effectively improve the prediction accuracy of the model.…”
Section: Introductionmentioning
confidence: 99%
“…After that, with the continuous precipitation of wax crystals, the solid particles will be gradually connected to form a spatial network structure, and the crude oil is wrapped in its pores, which results in a deterioration of flows and eventually causes the blockage of the pipeline. It is concluded that the wax deposition process is influenced by many factors, such as crude oil composition, pipe wall material, temperature, , flow velocity, and flow pattern. , For the wax deposition mechanism, the classical theories include molecular diffusion, , shear dispersion, , Brownian motion, , and gravity deposition. , Recently, with the further development of the wax-deposited research, the mechanisms of shear stripping, gelation (emulsified nucleation) and aging was proposed. , Many scholars have performed research regarding those mechanisms. Hoffmann et al and Mehrotra et al found that the carbon number distribution on the surface of wax deposition layer is closer to that of the flowing oil when the flow rate is low and the water content is high.…”
Section: Introductionmentioning
confidence: 99%